Politics and Law of Sports Business (Sport Industry) After the Ratification of Law no. 11 of 2022 - Nadiasa, I Ketut; Kurniawan, I Gede Agus (SASI, 2024)
Introduction: The development of the sports industry inherently provides opportunities related to economic orientation and job creation within the sports industry.Purposes of the Research: This study focuses on analyzing the legal-political aspects in sports law following the enactment of the Sports Law. The research aims to address two legal issues: (i) issues concerning the sports industry within the Sports Law, and (ii) the legal-political dynamics of the sports industry within the Sports Law and future regulatory efforts.Methods of the Research: This research employs a normative legal research approach, emphasizing conceptual and legislative analysis.Results of the Research: There are three issues and weaknesses in the regulation of the Sports Law concerning the sports business: the lack of provisions regarding the empowerment of micro, small, and medium enterprises (MSMEs) in the sports business sector, the non-integration of sports law regulations with general business regulations potentially leading to regulatory overlaps that hinder sports business operations, and the partial nature of corporate social responsibility regulations in aiding sports development, limited to financial contributions by sports entities. Generally, the legal-political framework of the sports industry under the Sports Law has provided regulations concerning sports business and involved parties. To optimize the legal-political framework of the sports industry, future regulatory efforts are needed to refine the Sports Law through revisions aimed at enhancing the sports business environment, accommodating meaningful participation from relevant stakeholders. Another critical aspect is the formulation of implementing regulations within the Sports Law, particularly those pertaining to the sports business, to ensure integrated regulations between sports-specific implementing rules and those of other sectors sharing similar business orientations.